ANALISIS POTENSI WISATA SEJARAH DAN BUDAYA UNTUK PENGEMBANGAN PARIWISATA BERBASIS KEARIFAN LOKAL DI NAGARI SITUJUAH BATUA - Najmi, Najmi; Novio, Rery; Hastuti, Hera; Yefterson, Ridho Bayu (Ensiklopedia of Journal, 2024)
Nagari Situjuah Batua, located in Situjuah Limo Nagari District, 50 Kota Regency, is a village that has a history that is quite different from other villages in West Sumatra. The history of this village is a major event and is always remembered by the people of Situjuah Batua itself. The event was the Situjuah Event. This event is always commemorated by the community every January 15. This event is a historical event that occurred during the Physical Revolution when the Indonesian Government maintained its independence from Dutch colonialism. The Situjuah incident can be said to be an event that paved the way for the Minangkabau people, especially the people in Nagari Situjuah Batua related to the betrayal committed by their own nation and the killing of heroes by the Dutch army. The commemoration of the event is not just an ordinary commemoration but also coincides with the "alek nagari" which has been routinely held since a long time ago. The commemoration of the Situjuah Event can be said not only to be commemorated as a ceremony to honor the fallen heroes, but also to commemorate a cultural attraction event in the form of "alek nagari". This memorial ceremony and "alek nagari" will be used as promising tourism potential, especially historical and cultural tourism. But this has not been realized by the wider community. In order for this potential to become a potential for historical and cultural tourism, further research is needed using a historical approach, namely tracing the traces of the Situjuah Event and making it a potential for historical tourism and juxtaposed with "alek nagari" which is also used as a cultural attraction as one of the potential for cultural tourism.Keywords: Potential Analysis, Historical and Cultural Tourism, Historical Traces